Cephalometric Hard and Soft Tissue Norms for Sudanese Adults - Salama, Eman I; Abuaffan, Amal H (Orthodontic Journal of Nepal, 2015)
Introduction: Cephalometric norms of various populations show differences between diverse ethnic and racial groups. Thus, numbers of cephalometric norms have been established for different ethnic groups. Objective: To assess skeletal, dental and soft tissue features in a sample of well-balanced face of Sudanese university students. Materials & method: Lateral cephalographs were taken from 18-25 years old 35 male and 38 female Sudanese university students with balanced facial profile and Class I occlusion with no previous orthodontic treatment. Fourteen angular and five linear measurements, and facial index were recorded according to Husund analysis. Male and female mean values were compared statistically using Student t-test. Result: Statistically significant differences were noted between both genders especially in skeletal variables SNA˚, SNB˚, SNPg˚, ML- NSL˚, NL-NSL˚, UFH, LFH and dental variable I -Ī. Holdaway angle showed no significant difference between the genders. Skeletally, maxilla and mandible of the Sudanese sample were more prognathic compared to Caucasians and Arabs but less prognathic than the Africans. Dentally, maxillary and mandibular incisors were more proclined compared to Arabs and Caucasians. Soft tissue analysis showed more lip protrusion in Sudanese adults. Conclusion: The study offered normative cephalometric standards for Sudanese adults, which were specific for each gender group. The normative values showed that the Sudanese sample lied between African and Arab values which might suggest that the studied sample had an Afro-Arabian mixture.